Language Propriety in Javanese - Poedjosoedarmo, Soepomo (Universitas Sanata Dharma, 2017)
This paper presents the principles of language propriety in Javanese. The principles presented here cover the speech components offered by Hymes. It discusses how an individual or P1 should behave as a participant in the social network in general and how one should do when engaging in a conversation with an interlocutor (P1 to P2). The discussion also points out what topic and aim of speech should be expressed and with what means of communication one should express it (S, E and I), how should the genre and the speech act be, how are the sentences to be expressed, and what words are to be used or to be avoided to suit the mood of the speech (G, A, and K). Furthermore, the paper also displays how the speech should be uttered and enunciated and how a person should handle his physical gestures to accompany the speech act (a part of N). Some key terms of language propriety in Javanese presented here are ramah, sabar, tepa slira, hormat, empan papan, nujuprana, and subasitaa.Keywords: propriety, Javanese, speech